Evaluation of Tissue Homogenization to Support the Generation of GMP-Compliant Mesenchymal Stromal Cells from the Umbilical Cord. (21st January 2016) - Emnett, Ryan J.; Kaul, Aparna; Babic, Aleksandar; Geiler, Vicki; Regan, Donna; Gross, Gilad; Akel, Salem
Abstract : Recent studies have demonstrated that the umbilical cord (UC) is an excellent source of mesenchymal stromal cells (MSCs). However, current protocols for extracting and culturing UC-MSCs do not meet current good manufacturing practice (cGMP) standards, in part due to the use of xenogeneic reagents. To support the development of a cGMP-compliant method, we have examined an enzyme-free isolation method utilizing tissue homogenization (t-H) followed by culture in human platelet lysate (PL) supplemented media. The yield and viability of cells after t-H were comparable to those obtained after collagenase digestion (Col-D). Importantly, kinetic analysis of cultured cells showed logarithmic growth over 10 tested passages, although the rate of cell division was lower for t-H as compared to Col-D. This slower growth of t-H-derived cells was also reflected in their longer population doubling time. Interestingly, there was no difference in the expression of mesenchymal markers and trilineage differentiation potential of cells generated using either method. Finally, t-H-derived cells had greater clonogenic potential compared to Col-D/FBS but not Col-D/PL and were able to maintain CFU-F capacity through P7. This bench scale study demonstrates the possibility of generating therapeutic doses of good quality UC-MSCs within a reasonable length of time using t-H and PL.